Clofazimine Enteropathy: A Rare and Underrecognized Complication of Mycobacterial Therapy. (2nd September 2016) - Szeto, Winnie; Garcia-Buitrago, Monica T.; Abbo, Lilian; Rosenblatt, Joseph D.; Moshiree, Baharak; Morris, Michele I.
Abstract: Clofazimine-induced crystal-storing histiocytosis is a rare complication of treatment previously reported in dermatology literature as a complication of leprosy therapy. We report a case of disseminated Mycobacterium abscessus requiring treatment with high-dose oral clofazimine resulting in enteropathy in a patient who presented with abdominal pain, malnutrition, and melena.